Prevalence and risk factors of type II endoleaks after endovascular aneurysm repair: A meta-analysis. - Qiang Guo; Xiaojiong Du; Jichun Zhao; Yukui Ma; Bin Huang; Ding Yuan; Yi Yang; Guojun Zeng; Fei Xiong (PLoS ONE, 2017)
Objectives This systematic review and meta-analysis aims to determine the current evidence on risk factors for type II endoleaks after endovascular aneurysm repair (EVAR). Materials and methods A systematic literature search was carried out for studies that evaluated the association of demographic, co-morbidity, and other patient-determined factors with the onset of type II endoleaks. Pooled prevalence of type II endoleaks after EVAR was updated. Results Among the 504 studies screened, 45 studies with a total of 36,588 participants were included in this review. The pooled prevalence of type II endoleaks after EVAR was 22% [95% confidence interval (CI), 19%-25%]. The main factors consistently associated with type II endoleaks included age [pooled odds ratio (OR), 0.37; 95% CI, 0.31-0.43; P<0.001], smoking (pooled OR, 0.71; 95% CI, 0.55-0.92; P<0.001), patent inferior mesenteric artery (pooled OR, 1.98; 95% CI, 1.06-3.71; P = 0.012), maximum aneurysm diameter (pooled OR, 0.23; 95% CI, 0.17-0.30; P<0.001), and number of patent lumbar arteries (pooled OR, 3.07; 95% CI, 2.81-3.33; P<0.001). Sex, diabetes, hypertension, anticoagulants, antiplatelet, hyperlipidemia, chronic renal insufficiency, types of graft material, and chronic obstructive pulmonary diseases (COPD) did not show any association with the onset of type II endoleaks. Conclusions Clinicians can use the identified risk factors to detect and manage patients at risk of developing type II endoleaks after EVAR. However, further studies are needed to analyze a number of potential risk factors.